2022
DOI: 10.53730/ijhs.v6n1.4488
|View full text |Cite
|
Sign up to set email alerts
|

Method of forming professional competencies future teacher for labor education

Abstract: The purpose of the article is to theoretical studying scientific developments and systematization of practical data on the features of acquiring skills in computer competence by digital technology specialists under the conditions of the pandemic. Societal challenges related to the digital transformation of the economy, production, management, and social relations undoubtedly affect the education system, primarily by changing approaches to the learning process. While in the conditions of evolutionary transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Studies revealed an intrinsic coupling mechanism between rural education and agricultural modernization development (Baeten et al, 2013;Bordiuk et al, 2022;Komilova et al, 2021;Tri et al, 2022). The ratio of the average years of education in the labor force and the number of rural scientific and technical personnel had a significant effect on the technical efficiency and labor productivity in agriculture (Burdette et al, 2011;Lesyk et al, 2022;Loccoh et al, 2021;Sribna et al, 2022;Wu & Kim, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies revealed an intrinsic coupling mechanism between rural education and agricultural modernization development (Baeten et al, 2013;Bordiuk et al, 2022;Komilova et al, 2021;Tri et al, 2022). The ratio of the average years of education in the labor force and the number of rural scientific and technical personnel had a significant effect on the technical efficiency and labor productivity in agriculture (Burdette et al, 2011;Lesyk et al, 2022;Loccoh et al, 2021;Sribna et al, 2022;Wu & Kim, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%